COMORBIDITIES AND QUALITY OF LIFE IN PEOPLE WITH STAGE 2 HYPERTENSION: A STUDY IN YOGYAKARTA, INDONESIA (Proceedings of the Global Public Health Conference, 2022)
Hypertension is a major public health issue throughout the world, including in Indonesia. Quality of life has been assessed in patients with hypertension, but few data have been reported from community settings. This study assessed the relationships between comorbidities and quality of life in people with stage 2 hypertension in an Indonesian rural community. This questionnaire-based study included 108 people (aged 45 years or older) living in a rural community who was diagnosed with stage 2 hypertension >6 months before the study began. The abbreviated version of the World Health Organization Quality of Life Instrument was applied to measure the quality of life.  This instrument comprises four domains of quality life: physical health, psychological health, social relationships, and environmental health. Among the 108 participants, 73 (67%) self-reported having the comorbid disease; cardiovascular diseases, endocrine disorders, and musculoskeletal disorders were the most common. Only 31 (29%) reported having a good quality of life in the physical health domain (score ³60 on the quality-of-life instrument). The percentages of participants reporting good quality of life were 37 (35%), 50 (47%), and 48 (44%) for the domain’s psychological health, social relationships, and environmental health domains, respectively. A higher score for the comorbidities index was associated with lower quality of life (p
Keywords: hypertension; quality of life; comorbidity; rural community